Stratigraphic succesion of the Upper Cretaceous fish assemblages of Kras (Slovenia) - Cavin, Lionel (Geologija, 2000)
In the paper new finds of Upper Cretaceous fossil fishes from five levels of the Komen and Tomaj limestones of Kras are discussed. The compositions of the fish assemblages are summed up and their precise stratigraphic position in the strata sedimented between the Cenomanian and Lower Campanian is given. About 74% of studied specimens were collected in the Santonian - Campanian Tomaj limestone in the area between Kazlje, Dobravlje and Tomaj and thus they represent a new fish assemblage if compared to the old collections that originate mainly from the Cenomanian beds of the Komen vicinity.
Keywords: apnenec; fosili; karst; Kras; kreda; Lake Kreda; ribe; Slovenia; Slovenija; stratigrafija; stratigraphy